PERAN PESANTREN DALAM MENGEMBANGKAN LITERASI DIGITAL SANTRI DI FORUM LINGKAR PENA (FLP) DARUL ULUM BANYUANYAR - Dewi Chairun Nisa; Ach Sya’roni (Universitas Islam Madura, 2023)
The Circle Pen Forum (FLP) was founded by the Darul Ulum Islamic boarding school so that the students are literate and numerate literate, the students are not only smart about religious knowledge but also socially smart. The focus of this research is FLP activities, forms of digital literacy that are applied, and challenges and solutions in implementing digital literacy. This research method uses a qualitative type of purposive sampling in data collection. Collecting data using interview techniques, observation, and analysis of documentation data. The data analysis is reduction, display, and verification. Triangulation, analysis of negative cases, and extension of the study to check the validity of the data. The results showed that there were four FLP activities, namely: daily activities, weekly activities, monthly activities, and annual activities of publishing anthologies and harlah. There are two types of digital literacy that are applied, namely searching for information via digital and then making it as study material, and writing works through blogs and websites. The obstacles are activities that are too dense, facilities and infrastructure, and the Islamic boarding school system which limits students from using digital media. The solution is to use a facilitator who has the authority to access digital media to track information and upload works to the FLP blog and website. The implication of this research is that students and pesantren residents can understand that Islamic boarding schools must be technologically literate, culturally and socially literate as a complement to religious literacy which is a distinct characteristic of Islamic boarding schools.